Peranan Faktor Karakteristik Individu dan Faktor Organisasi terhadap Kinerja Pegawai Dinas Pertanian Tanaman Pangan Provinsi Bali - A.A ISTRI WINDA NOVITASARI; MADE ANTARA; I MADE SUDARMA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract The Role of Individual Characteristic Factor and Organization Factor Toward The Performance of Agricultural Office Province Bali The Agricultural Office Province Bali is one of government’s institution that organize the management duty of agricultural program and the other duties relate to the agriculture field in serving the needs of farmer’s input usage for increasing the agricultural production which is done. This research is aimed to confirm and know the role of respondent characteristic factor and organization factor toward the officers’s performance of Agricultural Office Province Bali. The kinds of data used were quantitative and qualitative. The methods of data analysis used were confirmatory factor analysis and qualitative descriptive. The result gotten from this research is the individual characteristic factor and organization factor have the same role or balance toward the officer’s performance of Agricultural Office Province Bali about 50%. Education degree sub-factor has the biggest role toward individual characteristic factor and the lowest role towards individual characteristic factor is gender sub-factor. Compensation sub-factor has the biggest role and discipline sub-factor has the lowest towards organization factor. Sub-factor which has the biggest role towards the officer’s performance factor of Agricultural Office Province Bali is compensation sub-factor. Sub-factors that have the second and third biggest roles are education degree sub-factor and age sub-factor. Sub-factor that has the lowest role towards the officers performance factor is sub-factor discipline. Keywords: confirmatory factor analysis, individual characteristic factor, organization factor, officer’s performance